2017
DOI: 10.3390/ijerph14030288
|View full text |Cite
|
Sign up to set email alerts
|

Pedestrians in Traffic Environments: Ultrafine Particle Respiratory Doses

Abstract: Particulate matter has recently received more attention than other pollutants. PM10 and PM2.5 have been primarily monitored, whereas scientists are focusing their studies on finer granulometric sizes due both to their high number concentration and their high penetration efficiency into the respiratory system. The purpose of this study is to investigate the population exposure to UltraFine Particles (UFP, submicrons in general) in outdoor environments. The particle number doses deposited into the respiratory sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 54 publications
(55 reference statements)
0
20
1
Order By: Relevance
“…A very high variability (215 %) is recorded for the particles in the size channel 11.5 nm, it means a fresh aerosol continuously emitted by sources but, different from what reported in previous study (Manigrasso et al, 2017a), the variability is always over 101 %, except in two cases (71 % at 15.4 nm and 75 % at 20.5 nm), showing a presence of possible different contributions over the combustion processes. Figure 6 shows the behavior of the UFPs at different sizes related to the total VOCs trend in the same period.…”
Section: Second Case Study: Walking and Breathing Around A Small Citycontrasting
confidence: 87%
See 1 more Smart Citation
“…A very high variability (215 %) is recorded for the particles in the size channel 11.5 nm, it means a fresh aerosol continuously emitted by sources but, different from what reported in previous study (Manigrasso et al, 2017a), the variability is always over 101 %, except in two cases (71 % at 15.4 nm and 75 % at 20.5 nm), showing a presence of possible different contributions over the combustion processes. Figure 6 shows the behavior of the UFPs at different sizes related to the total VOCs trend in the same period.…”
Section: Second Case Study: Walking and Breathing Around A Small Citycontrasting
confidence: 87%
“…On the other hand, a NanoScan SMPS (model 3910, TSI), was also used for measuring particle number concentrations in the range 10-365 nm (divided in in thirteen size channels) by means of a scanning mobility particle sizing technology with 60 s time resolutions (Manigrasso et al, 2017a). The NanoScan SMPS is ideal for applications that demand portability like on-road measurements, workplace surveys, field studies, and point source identification.…”
Section: Measurementsmentioning
confidence: 99%
“…Many studies have reported that effects of traffic-related pollution are more severe on people who are suffering from chronic obstructive pulmonary disease (COPD). A recent study reported that COPD-affected individuals received greater doses of UltraFine Particles (UFP) than healthy individual due to their higher respiratory rate [38]. Therefore avoiding exposure to air pollutants is important for individuals with COPD.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, at the morning rush hour, in the 2 h time interval of Figure 9 from 08:00 to 10:00, 2.42 × 10 10 particles were deposited in the respiratory system, of which 28%, 25%, and 47% respectively in the H, TB and Al regions. Note that such estimates are based on measurements carried out at a fixed location, and thus do not account for the peak-exposures possibly experienced in proximity of traffic [69,70].…”
Section: Day Of Sampling Totalmentioning
confidence: 99%